The Supply Side of Innovation: H‐1B Visa Reforms and U.S. Ethnic Invention - Kerr, William R.; Lincoln, William F. (Journal of Labor Economics, 2010)
This study evaluates the impact of high-skilled immigrants on U.S. technology formation. We use reduced-form specifications that exploit large changes in the H-1B visa program. Higher H-1B admissions increase immigrant science and engineering (SE) employment and patenting by inventors with Indian and Chinese names in cities and firms dependent upon the program relative to their peers. Most specifications find limited effects for native SE employment or patenting. We are able to rule out displacement effects, and small crowding-in effects may exist. Total SE employment and invention increases with higher admissions primarily through direct contributions of immigrants. (c) 2010 by The University of Chicago. All rights reserved.